Barriers to adult immunization and solutions: Personalized approaches. Issue 1 (2nd January 2017) - Alici, Devrim Emel; Sayiner, Abdullah; Unal, Serhat
ABSTRACT: Immunization is an important component of preventive healthcare services aiming to prevent and eventually eradicate infectious diseases by immunizing people before they become infected. Although immunization is an integral part of children's healthcare, this fact is underrated, even ignored in adults. In Turkey, adult immunization is available only for certain high risk groups such as health care professionals and populations aged > 65 y and under certain conditions including pregnancy, military service, travel-pilgrimage, and employment procedures. The fact that diseases such as pneumococcal pneumonia, influenza, rubeola, varicella, hepatitis A, and tetanus, which could be associated with severe complications in adults, are vaccine-preventable indicates the importance of adult immunization. In addition to the healthcare providers' knowledge about immunization, effective policies of related professional associations and the management of this issue by regulatory authorities, people's awareness in protecting their own health is of utmost importance in achieving the targeted level of adult immunization. This article focuses on the characteristics of the individuals as one of the 3 main cornerstones (individual, healthcare providers, regulatory authorities and supporting organizations) of immunization practices and discusses barriers to adult immunization and recommends solutions.